Phylogrouping and characterization of Escherichia coli isolated from colonic biopsies and fecal samples of patients with flare of inflammatory bowel disease in Iran - Nadalian, Banafsheh; Nadalian, Bahareh; Houri, Hamidreza; Shahrokh, Shabnam; Abdehagh, Mohammad; Yadegar, Abbas; Ebrahimipour, Gholamhossein (Frontiers in Medicine, 2022)
Background: Although the etiopathogenesis of inflammatory bowel disease (IBD) is still poorly understood, Escherichia coli has been described as a potential causative microorganism in IBD pathogenesis and also disease progression, offering a potential therapeutic target for disease management. Therefore, we conducted this study to investigate the pathotypes, phylogenetic groups, and antimicrobial resistance of E. coli isolates from patients with IBD in Iran. Methods: Fecal and biopsy colonic samples were collected from IBD patients experiencing flare-up episodes referred to Taleghani hospital in Tehran, Iran, between August 2020 and January 2021. Identification of E. coli strains was performed based on biochemical and molecular methods. Antibiotic susceptibility testing was performed as recommended by the Clinical and Laboratory Standards Institute. Phylogrouping and pathotyping of each isolate were carried out using polymerase chain reaction (PCR) and multilocus sequence typing (MLST) assays. Results: A total of 132 non-duplicate E. coli strains were isolated from 113 IBD patients, including 96 ulcerative colitis (UC), and 17 Crohn’s disease (CD) patients. In our study, 45% of CD-related E. coli and 43.7% of UC-related isolates were non-susceptible to at least three or more unique antimicrobial classes, and were considered as multidrug-resistant (MDR) strains. E. coli strains exhibited a high level of resistance to cefazolin, ampicillin, tetracycline, ceftazidime, ciprofloxacin, and cefotaxime. Enterotoxigenic E. coli (ETEC) and diffusely adherent E. coli (DAEC) were the most prevalent pathotypes, and groups B2 and D were the predominant phylogroups. Conclusions: In the present study, we found that E. coli strains that colonize the gut of Iranian patients with IBD most frequently belonged to phylogenetic groups B2 and D. We also conclude that E. coli isolates from IBD patients have been revealed to be resistant to commonly used antibiotics, in which most of them harbored strains that would be categorized as MDR.